COMPARATIVE ANALYSIS OF GERMANY'S INVESTMENT STRATEGY IN CENTRAL ASIA: A CLOSER LOOK AT KAZAKHSTAN AND UZBEKISTAN (Spectrum Journal of Innovation, Reforms and Development, 2024)
Germany's investment footprint in Central Asia, particularly in Uzbekistan and Kazakhstan, marks a significant pivot towards tapping into the region's burgeoning economic landscape. Over the past two decades, Central Asia has undergone remarkable transformations, demonstrated robust growth trajectories, and emerged as a dynamic player on the global economic stage. Despite a regional GDP that has soared to $347 billion in 2022 through an average annual growth rate of 6.2%, and a population nearing 77 million with a 2% annual increase, Central Asia remains underappreciated in its economic potential by the broader international community. This narrative is gradually shifting as foreign direct investment (FDI) in the region has reached an impressive $211 billion, with trade turnover multiplying sixfold since the turn of the millennium. This analysis zeroes in on Germany's strategic engagement with Central Asia, focusing on its investment ventures in Uzbekistan and Kazakhstan. These two nations stand out due to their strategic geographic positioning, economic reforms, and pivotal roles in fostering regional integration and connectivity. Germany's investment strategy in these countries is emblematic of a broader recognition of Central Asia's strategic importance in the Eurasian corridor, leveraging the region's transit potential and burgeoning markets.